I18 The national congenital anomaly and rare disease registration service (ncardrs): the first year. (12th March 2018) - Ward-Platt, M; Stevens, S; Miller, N
Abstract : Background: Congenital anomalies (CA) cause around a fifth of infant deaths and are a major contributor to subsequent illness and disability. Regional registers of CA have existed for over 30 years but an effective national registration system has long been needed. More recently, in recognition that collectively Rare Diseases are thought to affect up to 3.5 million people in UK, rare disease registration has been planned which will align with parallel European initiatives. Methods: From April 2015 Public Health England launched NCARDRS, incorporating the 7 existing regional CA registers and the National Down Syndrome Cytogenetic Register. Those regions not previously covered (51% of England) were added. A central database was developed for the accrual of new cases and into which to import data held in the pre-existing registers. New data sources for case ascertainment and import of supporting data, such as cytogenetic laboratory feeds, links to BadgerNet neonatal, and Hospital Episode data, have been developed. Pilot work and database development for Rare Disease ascertainment is ongoing. The analysis we report was based on data aggregated from 4 of the pre-existing NCARDRS regions. Results: There were 2905 cases with at least one congenital anomaly among 1 41 474 (21%) of births in England in 2015. CA accounted for 17% of infant deaths, half of which were from cardiac anomalies. Two thirds of anomalies were diagnosed prenatally; of those diagnosed postnatally for which there was information on timing, three quarters were diagnosed in the first postnatal week. Rates of non-genetic anomalies were significantly higher in mothers<20 years (201 per 10, 000 [95% CI: 164 to 245]) compared to the mean for all ages (147 per 10, 000 [95% CI: 141 to 154]). The birth prevalence of Edwards' syndrome increased on average by 1.2% (95% CI: 0.2% to 2.3%) per year between 2005 and 2014. Conclusion: The development of an effective national CA registration system has proved feasible, and reporting for the whole of England should be possible from the 2017 birth cohort onwards. Accurate national surveillance and monitoring of congenital anomalies and rare diseases is set to become a powerful tool to address child morbidity and mortality.